Clinical observation of familial cases of congenital ichthyosis - Nailya R. Pimenova; Elena I. Kashirskaya; Anastasiya V. Alekseeva (Педиатрическая фармакология)
Background. Ichthyosis is a group of rare genetic diseases with a wide phenotypic spectrum, characterized most often by generalized hyperkeratinization and desquamation with variable erythema [1]. In most cases, the diagnosis is established immediately after birth on the basis of clinical data. The basis of treatment is correct skin care, regular moisturizing, prevention of infection. Case Reports. The article describes clinical cases of congenital ichthyosis in two boys from the same family born 8 years apart. At the time of birth, both children had similar clinical signs and the disease progression types. Conclusion. Children in this family showed a genetically similar form of congenital ichthyosis. Due to timely initiation of complex treatment and correct skin care, there was a significant favourable evolution.